PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT ASTRA INTERNATIONAL DAIHATSU, TBK CIBUBUR - Firman Eksan; Donny Dharmawan (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
The purpose of this study was to determine the effect of competence and motivation on employee productivity of PT. Astra International Daihatsu, Tbk Cibubur. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population of all employees of PT. Astra International Daihatsu, Tbk Cibubur, amounting to 57 employees. The sampling technique of this study uses saturated sampling, which is the technique of determining the sample when all members of the population are sampled. Result competence and motivation have a positive and significant effect on the Employee Productivity of PT. Astra International Daihatsu, Tbk Cibubur, both partially and simultaneous.